2017
DOI: 10.1080/0167482x.2017.1289369
|View full text |Cite
|
Sign up to set email alerts
|

Whose fault is it? Blame predicting psychological adjustment and couple satisfaction in couples seeking fertility treatment

Abstract: Infertility bears psychological and relational consequences for couples who face this problem. Few studies have examined the role of self- and partner blaming to explain psychological and relationship adjustment in couple presenting with a fertility problem. This study used a dyadic approach to explore the links between blaming oneself and one's partner and both partners' symptoms of depression and anxiety, and couple satisfaction in 279 couples enrolled in fertility treatments. Partners were questioned about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 51 publications
3
37
1
3
Order By: Relevance
“…Hence, it is possible to assert that the difference between wives and husbands as regards marital adjustment is partially connected to the different strategies female and male partners adopt in order to cope with the infertility experience and, therefore, to the different impact that infertility has on the individual well-being of women and men. Indeed, although some studies underscored that the infertility condition affects the psychological well-being of both women and men (Schmidt, 2006; El Kissi et al, 2013; Péloquin et al, 2018), the majority of studies today are in agreement that the infertility experience is more stressful for women than for men, with infertile women generally reporting more stress regarding their condition (Berghuis and Stanton, 2002; Peterson et al, 2008; Ying et al, 2015; Greil et al, 2018; Kroemeke and Kubicka, 2018). At the same time, according to researchers who do not find differences between the partners, it is possible that the stress and emotional hardship connected to the experience of infertility are shared by the partners through a spill-over effect from one partner to the other, and that, for this reason, couple adjustment also presents similar levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, it is possible to assert that the difference between wives and husbands as regards marital adjustment is partially connected to the different strategies female and male partners adopt in order to cope with the infertility experience and, therefore, to the different impact that infertility has on the individual well-being of women and men. Indeed, although some studies underscored that the infertility condition affects the psychological well-being of both women and men (Schmidt, 2006; El Kissi et al, 2013; Péloquin et al, 2018), the majority of studies today are in agreement that the infertility experience is more stressful for women than for men, with infertile women generally reporting more stress regarding their condition (Berghuis and Stanton, 2002; Peterson et al, 2008; Ying et al, 2015; Greil et al, 2018; Kroemeke and Kubicka, 2018). At the same time, according to researchers who do not find differences between the partners, it is possible that the stress and emotional hardship connected to the experience of infertility are shared by the partners through a spill-over effect from one partner to the other, and that, for this reason, couple adjustment also presents similar levels.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, infertility represents a stressful condition, if not a traumatic one, for those who want to have a child because it is associated with the loss and grief connected with not being able to conceive naturally (Koert and Daniluk, 2018). Previous studies reported that the condition of infertility affects the psychological well-being of both women and men, which can feel like depression, guilt, anxiety, and isolation (Schmidt, 2006; El Kissi et al, 2013; Péloquin et al, 2018). If infertility-related distress impacts the quality of life of both partners (Maroufizadeh et al, 2015; Martins et al, 2016), some gender differences are reported (e.g., Ying et al, 2015): infertile women seem to feel more stress about their condition and to experience more depressive symptoms than infertile men (e.g., Berghuis and Stanton, 2002; Kroemeke and Kubicka, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It has been confirmed that just like women, men often experience damage to self-esteem [19] and feel inadequacy in relation to their social and familial role in the case of infertility [20], but the commonly used coping strategies are different among men and women [21]. Men tend to cope by increasing their involvement in work and other activities; they are more problem-solving oriented and tend to suppress their emotions in an effort to support their wives [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] Couple relationships are also often negatively impacted. 7 In light of the significant psychological burden associated with infertility, a number of studies have aimed to test the efficacy of various psychological interventions in improving mental health and relationship quality in this population, with mixed findings. Two systematic reviews of this literature have been conducted in the last 5 years, however, each coming to fairly disparate conclusions.…”
Section: Introductionmentioning
confidence: 99%